Foam‐Mat Drying of Cantaloupe (Cucumis melo): Optimization of Foaming Parameters and Investigating Drying Characteristics. Issue 6 (3rd December 2014) - Salahi, Mohammad Reza; Mohebbi, Mohebbat; Taghizadeh, Masoud
Abstract: In the present study, foam‐mat drying technique is used to dry cantaloupe pulp into powder. Foaming conditions, namely amount of egg white powder, xanthan gum and whipping time, optimized using response surface methodology for minimizing foam density and drainage volume. To evaluate drying behavior of the optimized foam, drying was carried out in a batch‐type thin‐layer dryer at three drying temperatures (40, 55 and 70C) on 3‐ and 5‐mm thicknesses. Ten thin‐layer drying models were evaluated in the kinetics research. Based on the statistic tests performed, Weibull distribution model can describe drying behavior of foams for all drying processes. Moreover, Fick's second law was employed to calculate the effective moisture diffusivity that varied from 3.283 × 10 −9 to 9.483 × 10 −9  m 2 /s and from 4.053 × 10 −9 to 1.216 × 10 −8  m 2 /s with activation energy values of 31.714 and 33.043 kJ/mol for foam thicknesses of 3 and 5 mm, respectively. Practical Applications: Cantaloupe ( Cucumis melo ) is a popular fruit and widely consumed in the world. Cantaloupe has many potential health benefits, but it is seasonal fruit and its shelf life is limited. Moreover, cantaloupe is sensitive to high‐temperature processes. Foam‐mat drying is an alternative for preservation of cantaloupe in the form of dried powder using medium temperatures. Cantaloupe pulp powder have a longer shelf life and may be a suitable source of β‐carotene and vitamin C. This powder, because of its ability to contribute special characteristics such as flavor, color and water‐binding properties to the final product, can be used as instant beverages, ingredients for bakery or extruded cereal products, ice cream, yogurt as well as pharmaceutical tablets.